Palladium Nanocubes as Saturable Absorbers for Mode-Locked Laser Generation at 1.56 μm - Zhe Kang; Fang Wang (Nanomaterials, 2024)
Palladium (Pd) nanocubes, a type of metallic nanostructure, have demonstrated remarkable optoelectronic properties, garnering significant attention. However, their nonlinear optical characteristics and related device applications remain underexplored. In this study, we report the fabrication of a novel saturable absorber (SA) by depositing Pd nanocubes onto a D-shaped fiber (DF). The Pd nanocubes, with an average size of 12 nm, were synthesized and integrated with a DF, resulting in a highly robust SA with broadband saturable absorption characteristics. When incorporated into Er3+-doped laser cavities, the Pd-DF SA enabled the generation of ultrafast pulses with a central wavelength of 1560 nm, a corresponding repetition rate of 26.7 MHz, and a temporal width of 1.85 ps. Our findings highlight the strong potential of the Pd-DF device as a versatile SA for constructing high-energy ultrafast fiber lasers.